Urinary Tract Infection - Califano, Paolo; Manzi, Joao; Abreu, Phillipe; Ordones, Flávio Vasconcelos [UNESP]; Silva, Rodrigo Guerra da [UNESP]; Kawano, Paulo Roberto [UNESP]; Slongo, Julio (Springer Nature, 2025)
Urinary tract infection is defined as a group of inflammatory reactions associated with microbiological aggression of the urothelium and underlying layers of the pelvic organs, generally followed by bacteriuria and pyuria. It composes a frequent reason for seeking urgent facilities and stands between the most common bacterial infections of the adult. They are also common in the hospital environment and may develop in patients admitted for non-urinary causes, especially in Intensive Care Units.